Effects of different levels of carotenoids and light sources on swordtail fish (Xiphophorus helleri) growth, survival rate and reproductive parameters. Issue 21 (2nd November 2021) - Rashidian, Ghasem; Rainis, Simona; Prokić, Marko D.; Faggio, Caterina
Abstract: In this trial, the interaction between two different light resource and different levels of two pigments was investigated in order to determine their effects on growth and reproductive performance of the ornamental fish swordtail ( Xiphophorus helleri ) broodstock. Fish were fed with different levels of 50, 100 and 200 mg · kg-1 of astaxanthin or canthaxanthin, under two different light conditions (natural and artificial). The obtained results were more evident in animals fed with astaxanthin in comparison to canthaxanthin. Furthermore, swordtails reared under artificial light in comparison to the natural light source showed better performance. Overall the greatest effect was for the fish treated with medium dose of astaxanthin (100 mg.kg-1), under the artificial light conditions of rearing. Results indicated the important effects of all three factors (light source, dosage and carotenoids type), with significant interactions between the carotenoid dosage with carotenoid type and light source. Graphical Abstract: